Hate Speech in the Comments’ Column Instagram: A Discourse Analysis - Mubarok, Yasir; Sudana, Dadang; Gunawan, Wawan (JOLLT Journal of Languages and Language Teaching, 2024)
The phenomenon of social media has undergone a transformation, serving as a platform for facilitating online commerce, exchanging ideas, disseminating information, and unfortunately, facilitating illicit activities such as fraud, intimidation, defamation, hate speech, and other related behaviors. The anonymity provided by social media platforms renders it a potent tool for disseminating harmful or discriminatory material. The purpose of this research is to describe hate speech directed at Putri Delina (PD) in her personal Instagram comment column. The descriptive qualitative research methods are used in this study. The main theory in this study is Searle's pragmatic speech act theory, and the data source is a screenshot of netizen comments on PD's Instagram account in 2022. The results of the study show that PD received hate speech in the comments section of her Instagram account. First, the expressive illocutionary, category-criticizing, found four data. Second, assertive illocutionary type, the state category, found one data. Third, the type of illocutionary commissive, swear category, found one data. Fourth, the illocutionary type of directive, the advising category, found three data. Last, the illocutionary type of declarative, the category of prohibit, found one data.